7+c+12=-4c+12

Simple and best practice solution for 7+c+12=-4c+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+c+12=-4c+12 equation:


Simplifying
7 + c + 12 = -4c + 12

Reorder the terms:
7 + 12 + c = -4c + 12

Combine like terms: 7 + 12 = 19
19 + c = -4c + 12

Reorder the terms:
19 + c = 12 + -4c

Solving
19 + c = 12 + -4c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '4c' to each side of the equation.
19 + c + 4c = 12 + -4c + 4c

Combine like terms: c + 4c = 5c
19 + 5c = 12 + -4c + 4c

Combine like terms: -4c + 4c = 0
19 + 5c = 12 + 0
19 + 5c = 12

Add '-19' to each side of the equation.
19 + -19 + 5c = 12 + -19

Combine like terms: 19 + -19 = 0
0 + 5c = 12 + -19
5c = 12 + -19

Combine like terms: 12 + -19 = -7
5c = -7

Divide each side by '5'.
c = -1.4

Simplifying
c = -1.4

See similar equations:

| 1=6(k+5) | | 7(x-4)=3(x-8) | | 4x+3=57-2x | | 2x-47=2(53)-47 | | 6r+11=15-r | | x^2+4x-94=0 | | 4-2(x+5)=4 | | 7(b-2)=4 | | 2(10-3d)+80= | | 3x+2-x=12 | | F(x+8)=3(x+8)-9 | | 7=8(r-6) | | 7(v+4)-3v=2(2v+2)-12 | | 0.04x^2-3.5x+100=10 | | 8x+17=5x+23 | | 18x+54=252 | | y=0.7x-3.6 | | 10+11x=-30+x | | -6(i-3)=2 | | 4x+6(x-4)=16 | | 22+4x=9x+2 | | -9(-6)-5(2)=12 | | 154x=462 | | -9(3)-5(-6)=12 | | 5x+5y+6z-2x+z-8y= | | 4=7(r-3) | | -36=3(x-3)-6x | | 4-5y=-20 | | 9=6(q-6) | | 0=-0.09+1.1x | | 7x-2(4x+23)+12= | | 5+7=2x |

Equations solver categories